E-marketing strategy of Mobile World Investment Corporation = Chiến lược tiếp thị điện tử của Công ty Cổ phần đầu tư Thế Giới Di Động. - Thái, Trung Hiếu (2020)
The thesis introduces the essentials of e-marketing and e-marketing strategy, the basic characteristics of it and compares the similarities and differences between e-marketing and traditional marketing as well as some other related concepts such as e-business, e-commerce... The thesis provides an overview of e-marketing and useful information for the constructing and developing process of the marketing strategy for the business. The thesis introduces some popular digital channels used all over the world. At the same time, the thesis presents and analyzes the development of e-marketing activities in Vietnam as well as within the scope of the Mobile World Investment Corporation in particular. The thesis discusses the status of e-marketing at the Mobile World Investment Corporation and provides analysis and evaluation of e-marketing strategy of the company. Based on that, the thesis proposes some solutions for Mobile World Investment Corporation to continue developing the e-marketing strategy so that business activities can continue to develop effectively.